Using 7E Method Learning Teaching About Derivative and indefinite Integration In Faculty of Education Souphanouvong University Academic Year 2019 - 2020 : https://doi.org/10.69692/SUJMRD080264 - PHATSOMBATH, Sengdao; VANG, Khammee; VONGSIPASEUTH, Bounmor; CHIACHERLAO, Fongyaneng; BOUNTHONG , Bounseng; PHONGSAVATH, Sengthavy (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
The purposes of this study were to: [1] investigate the E.I.(Effectiveness Index) of teaching and learning Derivative and indefinite Integration through 7E (7-E Learning Cycle) technique. [2] investigate students’ satisfaction toward teaching and learning Derivative and indefinite Integration, through 7E technique. The sample group of this study were the second year students majoring in Mathematics and physics in Faculty of Education Shouphanouvong University academic year 2019-2020. The research instrument were pre-test, post –test and questionnaires. The statistics model used for this study was SPSS program. The results of this study were regarded to the E.I. of teaching and learning Derivative and indefinite Integration through 7E technique consequence that E.I.= 0.5484, this meant that it is significantly higher than criterial and students’ satisfaction toward teaching and learning Derivative and indefinite Integration through 7E technique on high level.